ANÁLISIS DE UN SISTEMA DE DISIPADORES DE CALOR PARA LA REFRIGERACIÓN TÉRMICA EN MÓDULOS DE BATERÍAS DE ION-LITIO TIPO 18650. - Rivera Yaguana, Jorge Alexander (2024)
Temperature is crucial to the performance and safety of lithium-ion batteries, which are critical in applications ranging from portable devices to electric vehicles due to their high energy density and long life. However, overheating during charging and discharging can reduce their lifetime, degrade their performance and even cause fires or explosions. This paper details the procedure used to evaluate the geometry and thermal behavior of a fin-cooled lithium-ion battery module. It focuses on mitigating risks by determining the heat generated and the maximum allowable temperature to avoid accidents. Using numerical simulations in SolidWorks® Thermal Simulation, key module characteristics such as thickness, length, spacing and number of fins are varied, and the results are then validated with analytical calculations. It was found that a circular aluminum module with 13 annular fins of 35 mm length and 1.5 mm thickness reaches a base temperature of 32.9 °C with a heat flux of 56 W in stationary regime, on the other hand, when re-evaluated for a time of 776 seconds for the transient regime a temperature of 29.51°C is found. This study provides crucial guidelines for the efficient design of cooling systems, ensuring the safe operation of batteries within safe thermal limits. Keywords: Battery module, SolidWorks Thermal Simulation, heat transfer.